2016
DOI: 10.1111/iej.12701
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for soft tissue retraction during periapical surgery using 3D technology: a case report

Abstract: The significance of proper soft tissue retraction in periapical microsurgery is underemphasized. Geometric data from CBCT scans may be harvested for a variety of uses, adding value to the examination. 3D printing is a promising technology that may potentially have many uses in endodontic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
23

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 49 publications
0
13
0
23
Order By: Relevance
“…Digital Imaging and Communications in Medicine (DICOM) data sets may be used to fabricate custom surgical guides for tissue retraction and root‐end location in teeth undergoing apical surgery (Patel et al . , Ye et al . ).…”
Section: Cbct For Pre‐surgical Assessmentmentioning
confidence: 99%
“…Digital Imaging and Communications in Medicine (DICOM) data sets may be used to fabricate custom surgical guides for tissue retraction and root‐end location in teeth undergoing apical surgery (Patel et al . , Ye et al . ).…”
Section: Cbct For Pre‐surgical Assessmentmentioning
confidence: 99%
“…Patel et al . () demonstrated the use of a 3D printed custom tissue retractor to enhance visualization and soft tissue handling during EMS on a maxillary incisor. These articles suggest exciting possibilities for future creative applications of 3D printing within the modern EMS concept.…”
Section: Review Of Endodontic Applicationsmentioning
confidence: 99%
“…4) designed a stent defining the upper and lower margins of the osteotomy, as well as the root resection site and angulation, resulting in increased clinical efficiency and precision, minimizing risk of sinus perforation. Patel et al (2017) demonstrated the use of a 3D printed custom tissue retractor to enhance visualization and soft tissue handling during EMS on a maxillary incisor. These articles suggest exciting possibilities for future creative applications of 3D printing within the modern EMS concept.…”
Section: Surgical Guidesmentioning
confidence: 99%
“…In some cases, the use of CBCT significantly enhanced the management of these surgical cases, allowing for the determination of tooth thickness, the nature of periapical lesions and the inclination of the root, all of which were relevant factors for preoperative assessment of the pulp surgery. The manufacture of 3D printed models and custom retractors shed light on how existing CBCT scans can be used to further improve patient management …”
Section: Scanning Imaging Technologymentioning
confidence: 99%